PENGARUH PEMANFAATAN VIDEO YOUTUBE DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Siti Ruqoyyah; Hana Sakura Putu Arga; Medita Ayu Wulandari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research is motivated by the low mathematical communication skills of prospective elementary school teacher students. The purpose of this study is to see the achievement and improvement of students' mathematical communication skills using YouTube videos and those using conventional learning. This study used a quasi-experimental method with a non-equivalent pretest and posttest control group design. The population in this study were all students of second semester elementary school teacher candidates at one of the private tertiary institutions in Cimahi City. While the sample in this study were 60 students of second semester elementary school teacher candidates. The instrument used in this study was a test of mathematical communication skills. The results showed: 1) achievement and improvement of mathematical communication skills using YouTube videos was better than conventional learning; 2) Students can be confident, active and motivated in learning mathematics with YouTube videos.